EXPERIMENTAL STUDIES OF THE COMPLEX STRUCTURE OF THE ELECTRO-EXPLOSIVE CONDUCTORS - Kucher, D.; Kucher, L.; Smyrynska, N.; Lyshak, H. (Systems and Technologies, 2021)
The development process of modern high-voltage systems is inextricably linked with the tasks of high-speed switching of high-density currents on various elements. The use of existing high-voltage switching means (relays, gas dischargers, contactors, varistors, etc.) for successive switching of elements in high-voltage systems is limited primarily by their high inertia and the impossibility of strict coincidence of voltampere characteristics when redistributing high-density currents inside various elements. Fast electrical explosion of thin conductors accompanied by a secondary breakdown of detonation products can be the most promising method of energy redistribution during successive switching of several elements. This effect occurs when sufficiently high current densities are introduced into a thin conductor (j≈107 A⁄сm2). The implementation of the fast electrical explosion mechanism is accompanied by expansion, transformation into a sol and loss of conductor conductivity in the nanosecond range, which may allow a chain of successive switching of various elements within the high-voltage system to be formed. In order to practically prove the applicability of this effect in high-speed switching installations, the results of experimental studies carried out in two stages are presented. At the first stage of the experiment, an electric explosion was applied to single conductors, with different melting temperature, cross-sectional area and length. The analysis of the obtained results showed that by changing the thermophysical and structural parameters of the conductors, it is possible to obtain the necessary values of the duration of the fast electrical explosion effect. At the second stage of the experiment, based on the results of the duration of the fast electrical explosion effect, a special complex structure of high-speed switching elements was investigated. The structure included lead wires acting as switches and tungsten conductors whose electrical explosion sharpened the pulse voltage applied from the generator. Analysis of the obtained data showed the possibility of creating a successive commutation at the expense of the electric explosion of lead conductors with subsequent breakdown of its detonation products. The results of experimental studies presented in the paper confirm the operability of theoretical methods related to the use of the phenomena of fast electrical explosion and secondary breakdown of detonation products to create high-speed switching elements of high-density currents.